A Study of the Impact location to the attitude of parents on pre-schooling children in Bharatpur Metropolitan ward no. 29 (earlier, Kabilas) - Sapkota, Ganga Prasad (Journal of Balkumari College, 2019)
This article discusses about the impact of families on pre-schooling children in Bharatpur Metropolitan ward 29 (Kabila VDC earlier). The convenient sampling method issued collect 92 samples. Face to face questionnaire schedule is used for data collection tools. Cross tab, descriptive as well as analytical research design is used. Pilot survey is also conducted for reliability of the data and Cronbach alpha is used for internal consistency and Eigen value is also tested. Similarly, validity factor analysis is used. To test the locational impact of families on their child, non-parametr·ic chi-square test and p-value are used. Hence, this research paper concluded that there is positivistic impact of location to their children.